Workplace Exercise and Educational Program for Improving Fitness Outcomes Related to Health in Workers: A Randomized Controlled Trial. Issue 3 (March 2015) - Vilela, Bianca Lima; Benedito Silva, Ana Amélia; de Lira, Claudio Andre Barbosa; Andrade, Marília dos Santos
Abstract : Objective: To investigate the effects of a workplace fitness and education program intervention on physical fitness of workers. Methods: Employees from a chemical plant ( n = 60) participated in a 4-month longitudinal study. They were randomly distributed in control and experimental groups. The experimental group had 4 months of exercise training in 15-minute sessions. The following evaluations were performed before and after the training period: body composition, localized muscle strength, and flexibility. Results: The experimental group showed a significant decrease in body fat (24.7%) and a significant increase in lean mass (6.1%), flexibility (17.9%), sit-up test performance (39.8%), and push-up test performance (29.8%) after the workplace fitness and education program compared with initial values. Conclusions: A structured program of physical exercise was effective in improving body composition, abdominal strength, upper limb strength, and flexibility in workers.